The Beneficial Impacts of COVID-19 Lockdowns on Air Pollution: Evidence from Vietnam - Hai-Anh H. Dang; Trong-Anh Trinh (Global Labor Organization (GLO), 2020)
Little evidence currently exists on the effects of COVID-19 on air quality in poorer countries, where most air pollution-linked deaths occur. We offer the first study that examines the pandemic's impacts on improving air quality in Vietnam, a lower-middle income country with worsening air pollution. Employing the Regression Discontinuity Design method to analyze a rich database that we compile from satellite air pollution data and data from various other sources, we find the concentration of NO2 to decrease by 24 to 32 percent two weeks after the COVID-19 lockdown. While this finding is robust to different measures of air quality and model specifications, the positive effects of the lockdown appear to dissipate after ten weeks. We also find that mobility restrictions are a potential channel for improved air quality. Finally, our back-of-the-envelope calculations suggest that two weeks after the lockdown, the economic gains from better air quality are roughly 0.6 billion US dollars.
Keywords: D00; H00; O13; Q50; 330; COVID-19; air pollution; mobility restriction; RDD; Vietnam